Contraceptive Usage Frequency and its Associated Factors Amongst Married Women in District Okara, Punjab - Sadia Irshad Leghari, Shamaila Zamir, Rabbiya Sarwar, Tazeem Akhter, Wardah Nisar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency and associated factors of contraceptives usage amongst married women in District Okara, Punjab. Methodology: To highlight the factors that have a positive impact in increasing the knowledge and all the barriers that hinder the usage of contraceptive a regional survey was conducted in which 350 married women 175 from rural and 175 from urban areas of Okara were selected through convenient sampling. Logistic regression was used in determination of the link between different explanatory variables with outcome variables that was the usage of contraceptives. Results: 37.42% women used contraceptives in both rural and urban areas of Okara. Different economic activity shaped by various social factors was pinpointed. Information, education and facts about modern birth control methods, women’s bodily autonomy and the need to have another newborn in future were a few of highlighted associated factors. Conclusions: This study depicts that women empowerment was consistently and positively linked with intention to use contraception. Moreover, updated and modern information related contraceptive services and personal motivation to have a child were the censorious factors in usage of present time contraceptive services. Hence these aroused problems need serious attention in formulating policies regarding maternal health in Pakistan. Keywords: Maternal health, contraceptive services, lady health care workers